MICRORNAS IN EXTRACELLULAR VESICLES: PERSPECTIVES AS NON-INVASIVE BIOMARKERS FOR BREAST CANCER (CIPEEX, 2025)
Breast cancer is one of the leading causes of mortality among women worldwide, representing a major public health concern. Despite technological advances in screening and diagnosis, such as mammography and biopsy, challenges remain in early detection and prognosis, particularly during the initial stages of the disease. In this context, new approaches that provide greater sensitivity, specificity, and minimal invasiveness are essential to improve clinical management and increase patient survival. In recent years, extracellular vesicles (EVs) have gained prominence in biomedical research due to their role as carriers of bioactive molecules, including microRNAs (miRNAs). These small non-coding RNAs are key regulators of gene expression, and alterations in their profiles have been associated with critical processes in tumor development and progression, such as cell proliferation, invasion, metastasis, and therapy resistance. Thus, the analysis of miRNAs contained in circulating EVs emerges as a promising alternative for early diagnosis and clinical monitoring of breast cancer. This study aims to investigate, through a systematic literature review, the potential of EV-derived miRNAs as non-invasive biomarkers for early detection, therapeutic response, and prognosis in breast cancer patients. It is expected that a panel of clinically relevant circulating miRNAs will be identified, contributing to improved diagnostic accuracy, personalized therapy, and better clinical outcomes, while complementing or even surpassing traditional methods and advancing precision medicine in breast cancer care.
Keywords: Breast cancer; xtracellular vesicles; MicroRNAs; Biomarkers